Short-chain dehydrogenase/reductase (SDR) relationships: a large family with eight clusters common to human, animal, and plant genomes. - Kallberg, Y; Oppermann, U; Jörnvall, H; Persson, B (2002)
The progress in genome characterizations has opened new routes for studying enzyme families. The availability of the human genome enabled us to delineate the large family of short-chain dehydrogenase/reductase (SDR) members. Although the human genome releases are not yet final, we have already found 63 members. We have also compared these SDR forms with those of three model organisms: Caenorhabditis elegans, Drosophila melanogaster, and Arabidopsis thaliana. We detect eight SDR ortholog clusters in a cross-genome comparison. Four of these clusters represent extended SDR forms, a subgroup found in all life forms. The other four are classical SDRs with activities involved in cellular differentiation and signalling. We also find 18 SDR genes that are present only in the human genome of the four genomes studied, reflecting enzyme forms specific to mammals. Close to half of these gene products represent steroid dehydrogenases, emphasizing the regulatory importance of these enzymes.